2017
DOI: 10.1007/s10584-017-2055-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing uncertainty of climate change impacts on long-term hydropower generation using the CMIP5 ensemble—the case of Ecuador

Abstract: This study presents a method to assess the sensitivity of hydropower generation to uncertain water resource availability driven by future climate change. A hydrology-electricity modelling framework was developed and applied to six rivers where 10 hydropower stations operate, which together represent over 85% of Ecuador's installed hydropower capacity. The modelling framework was then forced with bias-corrected output from 40 individual global circulation model experiments from the Coupled Model Intercomparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 32 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…Crude oil and fossil fuels were given significant incentives for production and trade. The electricity sector pursued a hydrothermal electricity mix, consisting of large scale hydropower and fossil-fuel-based thermal-electric plants [15,16]. This period of neoliberalism lasted for nearly three decades, from 1979 until 2007.…”
Section: Energy and The Ecuadorian Political-economic Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Crude oil and fossil fuels were given significant incentives for production and trade. The electricity sector pursued a hydrothermal electricity mix, consisting of large scale hydropower and fossil-fuel-based thermal-electric plants [15,16]. This period of neoliberalism lasted for nearly three decades, from 1979 until 2007.…”
Section: Energy and The Ecuadorian Political-economic Contextmentioning
confidence: 99%
“…The concept of 'energy matrix change' or 'energy transition' has legitimised the new energy policy by promising a gradual increase of the share of renewable energy [15,16]. This increase of renewables is intended mainly to be implemented by the electricity sector, by decreasing fossil fuel-based thermal-electric plants and investing in eight new hydropower plants, the latter funded mainly by the pre-sales of crude oil to the Chinese government [17].…”
Section: Energy and The Ecuadorian Political-economic Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the effects of future climate change on hydropower resources introduce another major source of uncertainty for the development of the sector; for instance, van Vliet et al [7] and Zhang et al [6] suggest an increase in hydropower potential in the high latitudes of the Northern Hemisphere (North of 55 • latitude) and tropical Africa and a decrease in the US, Southern Africa, Europe and Southern Latin America. Carvajal et al [12] estimated uncertainty in annual hydropower generation in Ecuador due to climate change at between −55% and +39% with respect to the average historical production. Turner et al [13] showed that there is no clarity regarding the impacts of climate on hydropower in Latin America, which increases or decreases depending on the specific basin.…”
Section: Introductionmentioning
confidence: 99%